Assessment of a fluoroquinolone, three beta-lactams, two aminoglycosides, and a cycline in treatment of murine Yersinia pestis infection. - Bonacorsi, S P (1994)
Amoxicillin, cefotaxime, ceftriaxone, gentamicin, doxycycline, and ofloxacin were active in vitro, like the reference drug streptomycin, against the virulent strain Yersinia pestis 6/69M. The comparative efficacies of these drugs in vivo were evaluated in a standardized and reproducible mouse model of systemic infection. Each antibiotic was injected intravenously once, at 24 h postinfection, and then repeatedly during 48 h. In vivo results were measured by counting the viable bacteria recovered from the whole spleens of mice sacrificed at selected times. All the drugs were manifestly successful; ceftriaxone, ofloxacine, and the reference drug were the most effective. Therefore, gentamicin and doxycycline could be used, depending on the clinical forms of the Y. pestis infection. Further investigations on beta-lactams, especially those used in the present study, could be carried out to confirm or not confirm their activities against Y. pestis. Ofloxacin appeared to be as active and to perform as rapidly as streptomycin in the treatment of murine Y. pestis infection, which is in agreement with the previous successes obtained with the use of fluoroquinolones in the treatment of murine infections caused by other pathogenic yersiniae.